Decoupled trends for electrical and thermal conductivity in phase-confined CNT co-continuous blends. Issue 3 (3rd July 2018) - Colonna, Samuele; Han, Zhidong; Fina, Alberto
Abstract: In the present work, the morphology and the electrical and thermal conduction properties of co-continuous poly(vinylidene fluoride) (PVDF), maleated polypropylene (PPgMA) and multiwall carbon nanotubes (CNT) nanostructured blends are investigated. CNT preferentially locates in the PPgMA phase and clearly causes a refinement in the co-continuous structure. Electrical conductivity experiments show that nanocomposites are well above the percolation threshold and evidence for one order of magnitude enhancement in conductivity for the co-continuous nanocomposites compared to the monophasic nanocomposites with the same CNT volume fraction. On the other hand, thermal diffusivity enhancement for the co-continuous blends is found lower than that for the monophasic nanocomposites at the same CNT volume fraction. An explanation is proposed in terms of large interfacial area, causing phonon scattering at the interface between immiscible PVDF and PPgMA domains. Results described in this paper open the way to the preparation of high electrical and low thermal conductivity materials with possible application as thermoelectrics. Graphical Abstract: